Probabilistic potential health risk quantification, hydrochemistry, driving forces of groundwater nitrate and fluoride in a typical irrigation district, Northern China. (1st December 2022) - Yang, Fan; Jia, Chao; Yang, Xiao; Yang, Haitao; Chang, Wenbo
Abstract: Groundwater is the foremost water source of agricultural irrigation areas in northern China. However, the problem from excessive geogenic fluoride and anthropogenic nitrate in groundwater and its potential health risks are often neglected. This paper aims to identify the health threats, water quality and hydrochemistry in Weibei Plain, northern China. A total of 50 water samples collected in May 2021 were assessed by hydrogeochemical analysis, the entropy weight water quality index method and probabilistic human health risk assessment based on Monte Carlo stochastic simulation. The results showed that the hydrochemical type of surface water and groundwater was mainly SO4 ·Cl–Ca·Mg type. The rock weathering and cation exchanges were found to the important processes influencing hydrochemistry. The quality of surface water was higher than that of groundwater, with Class IV and Class V groundwater samples concentrated in the northwest of the study area. The F − concentration in groundwater samples generally exceeded the drinking water standard, which mainly came from mineral dissolution affected by excessive irrigation. Nitrate pollution in groundwater has regional characteristics, mainly from agricultural activities. Long−term use of groundwater might bring risks to residents' health, because more than 65% and 23% of groundwater samples exceeded the acceptable non−carcinogenic risk limits of F − and NO3 − to children, respectively. Considering the uncertainty of model parameters, children will have a probability of more than 46.9% and 12.6% to face F − and NO3 − risks in groundwater. Compared with NO3 −, the high concentration of F − in groundwater posed a higher threat to human health, and children faced higher risks. Compared with the deterministic method, the stochastic simulation can more accurately reflect health risks. The findings of this study can help policymakers devise strategies to ensure a safe supply of domestic water. Graphical abstract: Image 1 Highlights: Probabilistic HHRA was formulated and can identified health risks more accurately. Geogenic fluoride show higher human health risks than anthropogenic nitrate. There existed differences in hydrochemistry and quality between groundwater and surface water. Fluoride and nitrate concentrations in groundwater were higher than Chinese guidelines.